2017
DOI: 10.5507/bp.2016.057
|View full text |Cite
|
Sign up to set email alerts
|

Starvation- and antibiotics-induced formation of persister cells in Pseudomonas aeruginosa

Abstract: Background. Planktonic stationary and exponential cultures of Pseudomonas aeruginosa are highly resistant to killing by bactericidal antimicrobials because of the presence of persisters, cells that are multidrug tolerant and play a key role in the recalcitrance of biofilm infections. Aim. The aim of this study was to investigate the formation of persister cells in P. aeruginosa stationary vs. exponential cultures using different class antimicrobials. Methods. The susceptibilities of P. aeruginosa PAO1 wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…A selection of 847 primary publications deemed relevant to the theme of antibiotic bacterial persisters were manually surveyed for quantitative data from work carried out in planktonic cultures. Numerical data were finally extracted from 187 articles [ 3 , 4 , 7 , 8 , 11 , 12 , 36 , 39 , 40 , 49 , 51 , 52 , 55 , 56 , 57 , 58 , 61 , 66 , 67 , 68 , 89 , 115 , 116 , 117 , 119 , 121 , 122 , 126 , 133 , 141 , 142 , 143 , 150 , 163 , 173 , 177 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 ,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A selection of 847 primary publications deemed relevant to the theme of antibiotic bacterial persisters were manually surveyed for quantitative data from work carried out in planktonic cultures. Numerical data were finally extracted from 187 articles [ 3 , 4 , 7 , 8 , 11 , 12 , 36 , 39 , 40 , 49 , 51 , 52 , 55 , 56 , 57 , 58 , 61 , 66 , 67 , 68 , 89 , 115 , 116 , 117 , 119 , 121 , 122 , 126 , 133 , 141 , 142 , 143 , 150 , 163 , 173 , 177 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 ,…”
Section: Methodsmentioning
confidence: 99%
“…Cells better suited to surviving transient exposure to high concentrations of antibiotics are slow-growing cells, which are a minority when the environmental conditions are conducive to rapid cell multiplication (e.g., exponential phase in batch cultures) [ 7 , 8 , 36 ]. When the surrounding milieu has been exhausted of nutrients, cell growth stagnates, and the cell fraction that persists to antibiotics is somewhat higher (e.g., in the stationary phase in batch cultures) [ 37 , 38 , 39 , 40 ]. Any microorganism will find itself in cycles continuously oscillating between these two extremes of cell growth [ 41 , 42 ] and henceforth surviving exposure to antibiotics (or any other toxins) with different degrees of success.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge there are no previous reports demonstrating P. aeruginosa persisters in presence of polymyxin B. Gentamicin has not been studied for persister formation in P. aeruginosa. However, Mlynarcik and Kolar (2017) have studied the formation of persister cells in P. aeruginosa PAO1 against various antibiotics including the aminoglycoside, tobramycin and polymyxin B [31]. They demonstrate that treatment of tobramycin (at 104 μg/mL, 80X MIC) resulted in complete killing of PAO1 at 24 h; while our study revealed that treatment of gentamicin (at 100 μg/mL, 100X MIC) resulted in relatively large population of PAW1 persisters at 24 h. Similarly, treatment of PAO1 with polymyxin B (at 64 μg/mL, 80X MIC) showed regrowth of the cells after 24 h, possibly due to mutation [31]; whereas our study showed a…”
Section: Plos Onementioning
confidence: 99%
“…Antibiotic treatment also leads to the formation of persister cells [63][64][65][66]. There are several mechanisms involved in the formation of persister cells upon exposure to chemicals or antibiotics, as explained in detail in the aforementioned references.…”
Section: Anti-persister Activity Of Ua-cs Nps Towards Antibiotic-indumentioning
confidence: 99%